An In Silico Approach to Evaluate the Diabetic Wound Healing Potential of Phenylethanoid Glycoside in Inhibiting the Receptor for Advanced Glycation End Products (RAGE) - Ritika Baidya; Biswatrish Sarkar (Medical Sciences Forum, 2023)
Diabetes mellitus (DM) is a chronic metabolic disorder and is associated with impaired wound healing. Non-healing leg and foot ulcers are a frequent significant consequence of diabetes and are caused by a combination of inadequate tissue perfusion, suppression of re-epithelialization, and poor collagen production. Receptor for Advanced Glycation End Products (RAGE) is a multiligand cell surface molecule that belongs to the immunoglobulin superfamily and is crucial in the pathophysiology of poor wound healing in diabetics. By inhibiting RAGE, a chronic non-healing wound is more likely to undergo angiogenesis, enhance blood supply to hypoxic areas of the wound, and decrease the pro-inflammatory reaction and pro-apoptotic signaling. Phenylethanoid glycosides (PhGs) are a class of natural glycosides that possess anti-diabetic, wound-healing, antimicrobial, anti-inflammatory, and antioxidant properties. Echinacoside, a phenylethanoid glycoside, has a promising role in wound healing by enhancing angiogenesis, promoting keratinocyte migration and proliferation, and enhancing neutrophil and macrophage activity. Consequently, molecular docking was performed to assess the interaction between Echinacoside and the RAGE receptor (PDB ID: 6VXG). The ligand and receptor had a strong binding interaction, as indicated by the lowest binding energy, which was found to be −6.1 kcal/mol. To further assess the activity of Echinacoside in diabetic wound healing, in vitro and in vivo studies are needed.